Influence of modified carbon substrate on boron doped ultrananocrystalline diamond deposition - Oishi, Silvia Sizuka; Silva, Lilian Mieko; Botelho, Edson Cocchieri [UNESP]; Rezende, Mirabel Cerqueira; Cairo, Carlos Alberto Alves; Ferreira, Neidenĉi Gomes (IOP Publishing, 2018)
Boron doped ultrananocrystalline diamond (B-UNCD) growth was studied on modified reticulated vitreous carbon (RVC) produced from poly(furfuryl alcohol) (PFA) resin with sodium hydroxide additions at two different heat treatment temperatures. The different amounts of NaOH in PFA (up to reaching pH values of around 3, 5, 7, and 9) aimed to neutralize the acid catalyst and to increase the PFA storage life. Besides, this procedure was responsible for increasing the oxygen content of RVC samples. Thus, the effect of carbon and oxygen coming from the substrates in addition to their different graphitization indexes on diamond morphology, grain size, preferential growth and boron doping level were investigated by FEG-SEM, x-ray diffraction and Raman spectroscopy. Therefore, B-UNCD films were successfully grown on RVC with pH values of 3, 5, 7, and 9 heat treated at 1000 and 1700 °C. Nonetheless, the higher oxygen amount during B-UNCD growth for samples with pH 7 and 9 heat treated at 1000 °C was responsible for the RVC surface etching and the decrease in the boron concentration of such samples. The cross section images showed that B-UNCD infiltrated at around 0.9 mm in depth of RVC samples while carbon nanowalls were observed mainly on RVC samples heat treated at 1000 °C for all pH range studied.
Keywords: HFCVD; reticulated vitreous carbon; ultrananocrystalline diamond